Essays in industrial organisation - Troya Martinez, M (2012)
The first chapter considers a common agency model where two competition authorities share information about a firm under investigation. It shows that information-sharing can sometimes be welfare detrimental unless the authorities coordinate their enforcement policies as well as share information. The reason behind is that the authorities may have different leniency levels and the firm may decide to provide less precise information to one in an attempt to appeal the other. Furthermore it shows that the authorities may want to distort their policies in order to prevent the firm from obscuring the information it provides. The second chapter studies the seller's incentives to provide misleading advice about complex goods such as consumer electronics, banking or phone services. It shows how the incentives to give biased and imprecise advice are affected by the possibility of ex-post litigation, when a court or consumer protection authority investigates how biased the advice is and penalises accordingly. It finds that a more biased advice will also be less precise, thus, a stricter punishment for deceiving consumers also increases precision. The third chapter analyses the impact of trade credit on a relational contract between two vertically related firms. The firms operate in an environment with unobservable shocks, like a developing country or a black market, which create moral hazard in the repayment decision. It shows that the quantity sold in the market will be distorted downwards in order to curb the constrained firm's incentives to steal the credit and derives the optimal repayment scheme.